2015
DOI: 10.1099/vir.0.067363-0
|View full text |Cite
|
Sign up to set email alerts
|

Equine herpesvirus type 1 replication is delayed in CD172a+ monocytic cells and controlled by histone deacetylases

Abstract: Equine herpesvirus type 1 (EHV-1) replicates in the epithelial cells of the upper respiratory tract and disseminates through the body via a cell-associated viraemia in monocytic cells, despite the presence of neutralizing antibodies. However, the mechanism by which EHV-1 hijacks immune cells and uses them as 'Trojan horses' in order to disseminate inside its host is still unclear. Here, we hypothesize that EHV-1 delays its replication in monocytic cells in order to avoid recognition by the immune system. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…These results suggest that EHV-1 binds to specific receptors on the cell surface of a small population of CD172a + cells. Recently, we demonstrated that EHV-1 replication was highly restricted in CD172a + cells in vitro (Laval et al, 2015a). We can now confirm that a block at the virus-binding level is partially responsible for the restricted viral replication in CD172a + cells.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…These results suggest that EHV-1 binds to specific receptors on the cell surface of a small population of CD172a + cells. Recently, we demonstrated that EHV-1 replication was highly restricted in CD172a + cells in vitro (Laval et al, 2015a). We can now confirm that a block at the virus-binding level is partially responsible for the restricted viral replication in CD172a + cells.…”
Section: Discussionsupporting
confidence: 69%
“…Whilst a small fraction of CD172a + cells show EHV-1 particles bound to their surface, we think that not all viral particles will be internalized, and that not all viral genomes will be delivered to the nucleus and initiate efficient viral replication. Indeed, amongst 15-20 % of CD172a + cells with virus particles attached, we previously found that only 4-8 % of cells were susceptible to EHV-1 infection, dependent of the EHV-1 strain used (Laval et al, 2015a;Laval et al, in preparation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, we believe that these results are due to differences in the replication kinetics of EHV-1 in target monocytic cells between the two strains. This hypothesis is based on a previous study by Laval et al (10) demonstrating that EHV-1 (97P70) replication was restricted and delayed in CD172a ϩ cells adherent to plastic and ongoing in vitro studies on the replication kinetics of EHV-1 (03P37) in monocytic cells indicating strikingly different outcomes (unpublished data). We think that the adhesion of EHV-1-inoculated CD172a ϩ cells to EC speeds up the viral replication machinery in CD172a ϩ cells inoculated with EHV-1 strain 97P70, but to a lesser extent in CD172a ϩ cells inoculated with EHV-1 strain 03P37.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that CD172a ϩ cells serve as a "Trojan horse" to facilitate the spread of EHV-1 to target organs and to evade immunosurveillance (10). This may contribute to the observation that current vaccines do not provide full protection against severe symptoms, as EHV-1 can cause viremia despite the presence of a virus-specific immune response in the horse (11)(12)(13).…”
mentioning
confidence: 99%